Development of Interactive Multimedia to Improve Digital Literacy In Understanding The Concept of Informatics Learning at SMPN 1 Monta - Syahraini Putri; Ita Fitriati; Wahyudin, Wahyudin; Ahyar, Ahyar (Yayasan Insan Mulia Bima, 2024)
The development of technology in the digital era has changed the way students learn today, they tend to have greater access to electronic devices, the internet, and various digital media, so that learning styles are more responsive to learning that uses technology. Learning media is used as one of the tools to increase interaction between educators and students in the learning process. The lack of learning media in the learning process results in the failure to achieve learning objectives. This study aims to describe the development process, validity, practicality, and effectiveness of interactive multimedia using the Smart Apps Creator application for use in informatics learning at SMPN 1 MONTA Class VIII. The development model used in this study is the ADDIE development model. Based on the assessment of material expert I, the percentage obtained was 88.24% and Material Expert II, the percentage obtained was 79.41%. Based on the validation assessment of media expert I with the percentage obtained was 93.75% and media expert II, the percentage obtained was 91.25%, that all media experts stated that interactive multimedia to improve understanding of informatics learning concepts at SMPN 1 MONTA that had been developed was declared very feasible for use. Meanwhile, the increase in digital literacy before and after the student test was carried out with an average score of 55.1 (before) and 84 (after).